The Social Link between Power and Fading in Social Thought - Theoretical Analysis - GHERRAZ , Taher; CHETIOUI , Rabia (Milev Journal of Research and Studies, 2020)
The Social Association in Sociology expresses a range of social relations that combine members of society or individuals belonging to the same social group. They are linked through various organizations and institutions of social upbringing. Their importance is the mutual exchange of these individuals for the continuation of this social bond But it may be strengthened and weakened by some changes to society such as social change, as confirmed by the early socialists such as Ibn Khaldun, Durkheim, Ferdinand Tunis, Louis Wirth and Charles Cooley. Social of piety in certain groups or communities and weaken the other and up to disintegration in some developed societies, because of the tyranny of individualism, rationality and special interests and causes of course vary from one environment to another. Based on the above, we seek through this article to analyze the different sociological approaches that dealt with the social association, especially the Western societies.